Major element geochemistry of tephra glass shards and age model construction in Baltic Sea sediment cores EMB201/13-4 and POS507/29-2 - Daniela J M Müller; Ina Neugebauer; Rebecca J Kearney; Markus J Schwab; Oona Appelt; Markus Czymzik; Jérôme Kaiser; Helge Wolfgang Arz; Achim Brauer (PANGAEA, 2025)
Two sediment cores were retrieved from the Western Gotland Basin in the Baltic Sea: long core EMB201/13-4 during the Elisabeth Mann Borgese Cruise in 2018 (using a gravity corer) and short core POS507/29-2 during the Poseidon Cruise in 2016 (using a multi corer). In contrast to long core EMB201/13-4, POS507/29-2 has an undisturbed sediment-water interface. The sediments of both cores are alternating between finely laminated, faintly laminated and homogenous sections. In the datasets we provide the first tephra results from the Baltic Sea derived from both cores, as well as new radiocarbon data and a new radiocarbon and tephra based age model for core EMB201/13-4. Samples between 220 cm and 400 cm were collected in the 549 cm long core EMB201/13-4 to search for cryptotephra and radiocarbon date the identified tephra horizons. In the 57 cm long core POS507/29-2, nearly the complete profile (0-55 cm) was analyzed to identify cryptotephra deposits. The analyses were performed to revise the existing Holocene age model of the Western Gotland Basin that is complicated by varying influx of old carbon and reservoir age changes through the usage of well-dated isochronous tie-points, i.e. tephra.